Numerical Methods for Option Pricing - Dokuchaev, Mikhail (Curtin University, 2021)
The thesis studies numerical method for solving partial differential equations arising in financial modelling. More precisely, the thesis is focused on methods of solutions of parabolic equations with state dependent coefficients describing the fair price for European options and American options with parameters that depend on the state price.